PERBANDINGAN PENGUMPULAN ZAKAT PADA BAZNAS KABUPATEN TANAH DATAR SEBELUM DAN SETELAH IMPLEMENTASI PERATURAN BAZNAS NOMOR 2 TAHUN 2016 - Nopiardo, Widi (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This study aims to compare the collection of zakat in BAZNAS Tanah Datar Regency before and after the implementation of BAZNAS Regulation Number 2, 2016 particularly on the Establishment and Work Procedures of the Zakat Collection Unit. The type of research is field research by using qualitative method. The place of research is in BAZNAZ, Tanah Datar Regency. Interviews and documentation were used as the technique of collecting data. The data were analyzed qualitatively. The finding reflects there was a significant decrease in the amount of zakat collection at BAZNAS in Tanah Datar Regency from 2016 to 2018, after the implementation of BAZNAS Regulation No. 2, 2016. The amount of zakat collection in 2016 was Rp. 9,687,841,423-. Meanwhile the amount of zakat collection in 2017 was Rp. 8,672,514,884-. It means the decline percentage from 2016 to 2017 was 10.48%. Whereas in 2018, the amount of zakat collection was also declined to Rp. 7,311,597,007,- with the decline percentage 15.69% from 2017.